STAGES AND SPECIAL FEATURES OF THE ADMINISTRATIVE REFORMS IN THE REPUBLIC OF UZBEKISTAN - ABDUKHALILOV, Abdulla (CENTRAL ASIA AND THE CAUCASUS, 2007)
For more than 16 years, Uzbekistan has been trying to modernize its sociopolitical and economic system. This process is encompassing all spheres of public life, particularly the administrative structures. It should be noted that reform of state administration is the most important prerequisite for enabling transformation of the political system as a whole. Uzbekistan’s vast and cumbersome bureaucratic machinery is hindering implementation of the reforms in the republic. The prevalent bureaucratic arbitrariness in the economic sphere could lead to the monopolization of property, the creation of non-market mechanisms for regulating the activity of economic agents, and a reduction in the inflow of investments into the country. Stagnation of the administrative reforms in the political sphere is delaying the adoption of progressive laws, blocking the implementation of the decisions taken, promoting the formation of corporate groups among government officials, and making it impossible to efficiently regulate certain social processes. Bureaucratic arbitrariness in the social sphere can hinder the implementation of various social programs, which might later discredit the state bodies. In order to analyze the problems and prospects of administrative reforms in Uzbekistan, we should take a look at the main conceptual models of efficient administration. The idea of forming an efficient administrative system goes way back into the distant past. It generates, we feel, from man’s need, as a social being, to provide himself with efficiently organized administration. This was precisely why, according to many academics, the first political studies were of an applied nature. It is interesting to note that one of the oldest conceptions of administration was developed in China, since it was precisely that model which presumed the formation of a hierarchal system of administration, as well as clear delimitation of powers. These two main aspects of the Chinese administration model point the way to forming the rudiments of a rational bureaucracy. But in contrast to the contemporary versions, the purpose of the Chinese administration model was not to resolve social problems, but to serve the emperor. At the end of the nineteenth-beginning of the twentieth centuries, new administration models began to appear aimed at resolving social problems. These models started with Max Weber’s conceptions. It was precisely his conception of “rational bureaucracy” in the 20th century that led to the appearance of new administration models. Different administration models were formed within the framework of such schools and trends as the classical school, the school of human relations, structural-functional trends, and so on.